Hein G. Kiessling, Faith, Unity, Discipline: The ISI of Pakistan - Mr. Attiq ur Rehman (CISS Insight Journal, 2017)
With a doctorate from Munich, Kiessling is a political scientist and a historian. He spent thirteen years of his life in Pakistan (1989 to 2002) and lived in Quetta for four years and nine years in Islamabad. More than a decade-long stay of Kiessling in Pakistan provided him enough time to observe the civil-military relations in the country and perceived role of intelligence agencies in Islamabad’s politics. The book contains a record of Kiessling’s observations and analyses which are heavily based on his views of Pakistan’s domestic politics and foreign policy. As the head of a German political foundation, the author was able to travel across the country and observe various political developments from close quarters, and cultivated good relations with politicians and retired military officers. Additionally, he was able to interact with several former officers of ISI and Pakistan’s military. The book is divided into twenty short chapters with five appendices. First chapter of the book gives the genesis of ISI when Major General Walter Joseph Cawthorne, a British officer who opted to serve in Pakistan after Partition, established and headed the agency for a few months in 1948. This chapter also gives the main objective of creation of Inter-Services Intelligence Directorate and the task given to it by the state, which was intelligence gathering outside Pakistan in India, particularly in the disputed territory of Jammu and Kashmir.